(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
According to Michail Bachtin, the characters of a novel are always thought and perceived as ‘others’, that is, as bodies in principle external to both reader and writer. The concept of ‘performance’, when applied to the act of reading, shows the limitation of this theory as it deconstructs the relationship between otherness and identity. In Samuel Beckett’s novel The Unnamamable the main character cannot be considered as an ‘other’ in Bachtin’s sense, and requires a different theory of character as an always changing ‘becomingother’ in the process of reading. A similar dynamic interaction between the representation and the presence of the character can be eventually detected in the ‘reverse trompe l’oeil’ technique adopted by the young American artist Alexa Meade.